An investigation on structural, electrical, magnetic and impedance behaviour of (1-x)Pb(Zr0.30Ti0.70)O3-(x)SmFeO3 solid solution. (August 2022) - Kaur, Randeep; Kaur, Anumeet
Abstract: A solid state reaction technique was used to synthesize solid solutions of (1- x )Pb(Zr0.30 Ti0.70 )O3 -( x )SmFeO3 (denoted as (1- x )PZT-( x )SF) in the composition series 0.05 ≤ x ≤ 0.20. Refinement of X-ray diffraction data using the Rietveld method and the appearance of A˝ and Á modes at 450–550 cm −1 and 700–850 cm −1 respectively in the deconvoluted Raman spectrum proposed the existence of tetragonal phase (P4mm) and monoclinic phase (Cm) in the series. The P-E and M-H hysteresis curves show that all the samples have ferroelectric and magnetic characteristics at room temperature. The ferroelectric-paraelectric phase transition occurs at a temperature of 690 K. Electrical characteristics have been investigated using impedance plots with the variation of frequency 100 Hz - 1 MHz and temperature 513–593 K. From the impedance data the character of Nyquist plots ascribed the existence of bulk and grain boundary contributions in the samples. The superimposition of normalised curves of impedance spectra and modulus spectra points out that the conductivity relaxation has been seen in all the samples. Graphical Abstract: ga1